2019
DOI: 10.1038/s41598-019-45136-9
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue Mast Cells Promote Human Adipose Beiging in Response to Cold

Abstract: In a recent study, repeated cold application induced beiging in subcutaneous white adipose tissue (SC WAT) of humans independent of body mass index. To identify factors that promote or inhibit beiging, we performed multiplex analysis of gene expression with the Nanostring nCounter system (the probe set contained genes for specific immune cell markers, cytokines, and chemokines) on the SC WAT from lean subjects. Multiple correlations analysis identified mast cell tryptase and CCL26, a chemokine for mast cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 42 publications
(42 reference statements)
2
26
0
Order By: Relevance
“…Consistent with this, we observed a numerical increase in BMI and proportion classified obese in MC high participants ( P = .061 and P = .051, respectively). MCs are increased in the white adipose tissue (WAT) of obese individuals, 46,47 and serum tryptase levels are increased in obese individuals 46 . MCs have been proposed as a potential cellular link between obesity and asthma, 48 although WAT MC‐related gene expression did not differ between asthma and non‐asthma in a study of Inuit residing in Denmark and Greenland, in contrast to IL‐6 mRNA which was increased in asthma WAT 49 .…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with this, we observed a numerical increase in BMI and proportion classified obese in MC high participants ( P = .061 and P = .051, respectively). MCs are increased in the white adipose tissue (WAT) of obese individuals, 46,47 and serum tryptase levels are increased in obese individuals 46 . MCs have been proposed as a potential cellular link between obesity and asthma, 48 although WAT MC‐related gene expression did not differ between asthma and non‐asthma in a study of Inuit residing in Denmark and Greenland, in contrast to IL‐6 mRNA which was increased in asthma WAT 49 .…”
Section: Discussionsupporting
confidence: 89%
“…As degranulation positively correlates with UCP1 suggests thermogenesis and beiging enhancement through histamine and secretion of other factors (91). However, these positive associations between mast cells and thermogenesis/beiging of WAT has been challenged.…”
Section: Mast Cellsmentioning
confidence: 99%
“…There is accumulating evidence supporting a role for MCs in the browning of white adipocytes. It has been found that repeated cold exposure promotes beiging of human subcutaneous WAT and it is associated with increases in adipose tissue MC recruitment [9]. Recently, Finlin et al reported that MCs release histamine in response to cold, and this mediator induces the expression of UCP1 that is capable of uncoupling mitochondrial oxidative respiration and generating heat [81].…”
Section: Role Of MC In At Browningmentioning
confidence: 99%
“…The primary mechanism of brown and beige adipocyte activation is via the sympathetic nervous system through norepinephrine action. Importantly, it has also been reported that MCs express β-adrenergic receptors and can respond to norepinephrine to degranulate and release histamine [9]. BAT is highly vascularized with a complex network of blood vessels, and when activated, there is an increase in blood flow [82].…”
Section: Role Of MC In At Browningmentioning
confidence: 99%
See 1 more Smart Citation